INSTRUMENTS FOR THE ASSESSMENT OF HOSPITALIZED PATIENTS IN PALLIATIVE CARE: INTEGRATIVE REVIEW - Bezerra, Tárcilla Pinto Passos; Nobre, Thaiza Teixeira Xavier; Pennafort, Viviane Peixoto dos Santos; Graça, José Ronaldo Vasconcelos da; Barra, Isabel Pires; Holanda, Gisele de Oliveira Mourão; Mendonça, Ana Elza Oliveira de (Cogitare Enfermagem, 2024)
Objective: to identify the instruments used to assess patients hospitalized in palliative care. Method: integrative literature review carried out in January 2024 on the online data platforms: National Library of Medicine and Latin America and the Caribbean Literature on Health Sciences (LILACS) and the virtual library Scientific Electronic Library Online. Twelve scientific articles were analyzed. Results: Sixteen instruments were identified, seven of them generic, four specific for people in palliative care, four specific for oncology patients and one for the diagnosis of COVID-19. The Palliative Performance Scale and Edmonton Symptom Assessment were the most used instruments in the studies and the most relevant aspects to be evaluated in patients receiving palliative care were functional capacity, physical and psychological symptoms and old age. Conclusion: The instruments were useful as they guided health professionals, assessed patients, and planned care and decision-making.